2017
DOI: 10.1002/ieam.1883
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in assigning endocrine-specific modes of action: Recommendations for researchers and regulators

Abstract: As regulatory programs evaluate substances for their endocrine disrupting properties, careful study design and data interpretation is needed to distinguish between responses that are truly endocrine-specific and those that are not. This is particularly important in regulatory environments where criteria are under development to identify endocrine disrupting properties to enable hazard-based regulation. Irrespective of these processes, most jurisdictions use the WHO/IPCS definition of an endocrine disruptor (ED… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 63 publications
(73 reference statements)
0
29
0
Order By: Relevance
“…Finally, issues were identified that aid in distinguishing between endocrineversus nonendocrine-specific responses. These crosscutting issues are broadly outlined below and discussed in detail in the associated companion papers (Coady et al this issue; Marty et al this issue; Mihaich et al this issue; Parrott et al this issue). …”
Section: Crosscutting Issues Relevant To the Evaluation Of Hazards Anmentioning
confidence: 99%
See 3 more Smart Citations
“…Finally, issues were identified that aid in distinguishing between endocrineversus nonendocrine-specific responses. These crosscutting issues are broadly outlined below and discussed in detail in the associated companion papers (Coady et al this issue; Marty et al this issue; Mihaich et al this issue; Parrott et al this issue). …”
Section: Crosscutting Issues Relevant To the Evaluation Of Hazards Anmentioning
confidence: 99%
“…The use of an AOP approach to assemble the lines of evidence that lead to an adverse effect helps to put into context the various mechanisms that may be responsible. This approach was used to examine 3 of the case study substances, EE2, propiconazole, and 17β-trenbolone (Supplemental Data S1, S3, and S5; Mihaich et al this issue). …”
Section: Crosscutting Issues Relevant To the Evaluation Of Hazards Anmentioning
confidence: 99%
See 2 more Smart Citations
“…In early 2016, the Society of Environmental Toxicology and Chemistry (SETAC) sponsored an international Pellston workshop focused on hazard‐ versus risk‐based approaches for the ecological assessment of endocrine‐active chemicals (Matthiessen et al ). For this comparative evaluation, workshop participants focused on several facets of endocrine‐active chemical assessments, including linkage of mechanistic data indicative of altered endocrine function to adverse outcomes (Mihaich et al ), limitations and proposed improvements in current screening and testing approaches (Coady et al ), attributes of endocrine‐active chemicals that might complicate test interpretation and prediction of hazard/risk (Parrott et al ), and population‐level effects of endocrine‐active chemicals (Marty et al ). To support and illustrate these analyses, relatively extensive literature reviews were conducted for 6 well‐established endocrine‐active chemicals that affect different pathways, endpoints, and/or species, including an estrogen receptor agonist (17α‐ethinylestradiol), a sex steroid synthesis inhibitor (propiconazole), a compound associated with the induction of intersex in invertebrates (tributyltin), a thyroid‐active substance (perchlorate), and chemicals that interact with the vertebrate androgen receptor as an antagonist (vinclozolin) or an agonist (17β‐trenbolone; Matthiessen et al ).…”
Section: Introductionmentioning
confidence: 99%